High in the sky: the black soldier fly (Diptera: Stratiomyidae) inhabiting the forest canopy in the central Amazon, state of Amazonas, Brazil - Soares, Matheus Mickael Mota; Barros, Luana Machado; Ale-Rocha, Rosaly (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Hermetia illucens (Linnaeus, 1758), the black soldier fly, has been recorded for the first time inhabiting the canopy in a primary forest area in the central Amazon, in the state of Amazonas, Brazil. This record shows that the species is able to colonize environments up to 40 meters high and that the larvae are able to decompose organic matter at different stratification levels.
Keywords: Hermetia illucens; Hermetiinae; Decomposers; Immatures